Harnessing outer membrane vesicles derived from Bordetella pertussis to overcome key limitations of acellular pertussis vaccines - Locati, Lucía; Bottero, Daniela; Carriquiriborde, Francisco; López, Oriana; Pschunder, Bernarda; Zurita, Eugenia; Martin Aispuro, Pablo; Gaillard, Maria Emilia; Hozbor, Daniela (Frontiers in Immunology, 2025)
Acellular pertussis (aP) vaccines have markedly reduced the global burden of severe pertussis. However, their limited ability to elicit mucosal and durable immunity has been linked to waning protection and sustained Bordetella pertussis circulation. Selective pressure exerted by widespread aP vaccination has contributed to the emergence and regional dissemination of pertactin-deficient (PRN−) strains, raising additional concerns regarding vaccine effectiveness. In this context, we investigated whether incorporating outer membrane vesicles (OMVs) derived from B. pertussis into the aP vaccine could enhance its immunological profile, specifically by promoting Th1/Th17 polarization, inducing tissue-resident memory (TRM) T cells, and broadening protective coverage to include PRN− isolates, while maintaining aP-induced immunity against lower respiratory tract colonization. Using a murine intranasal challenge model with a two-dose vaccination schedule, we assessed the safety, immunogenicity, and protective capacity of the OMV+aP vaccine prototype (combined) versus aP vaccine. The combined formulation was well tolerated and induced robust systemic and mucosal responses, characterized by higher IgG2a/IgG1 ratios, increased Th1/Th17 cytokine production (IFN-γ, IL - 17, and IL - 22), and elevated anti-B. pertussis IgA titers. Flow cytometric analyses revealed lung- and nasal-resident CD4+ TRM cells in the combined immunized mice, which were absent in those receiving aP alone. Functionally, OMV+aP formulation conferred superior protection in pulmonary and nasal compartments, significantly reducing lung bacterial loads (including against PRN− strains) and uniquely diminishing nasal colonization even under high-dose challenge conditions. Passive transfer experiments confirmed the role of cellular and humoral immunity in bacterial clearance. These results demonstrate that OMVs synergize with aP to enhance immune response magnitude and quality, addressing key gaps in current aP vaccines and offering a next-generation strategy to prevent both disease and transmission.